The Impact of Digital Financial Literacy and Information Security on Non-Cash Payment Adoption among Students in Jakarta: The Moderating Role of Gender - Santi Dwi Mulyati; Natalia Caroline (PT. Hasba Edukasi Mandiri, 2026)
This study investigates the effect of digital financial literacy and information security on non-cash payment adoption among university students in Jakarta, with gender examined as a moderating variable. A quantitative research design was employed using survey data collected from 50 students who actively use non-cash payment instruments. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The findings reveal that digital financial literacy has a positive and statistically significant effect on non-cash payment adoption, indicating that students with higher levels of digital financial understanding are more likely to adopt cashless payment systems. In contrast, information security does not show a significant direct effect on non-cash payment adoption. Furthermore, the moderation analysis demonstrates that gender does not significantly moderate the relationship between digital financial literacy and non-cash payment adoption, nor between information security and adoption behavior. These results suggest that non-cash payment adoption among students is primarily driven by cognitive and capability-related factors rather than demographic differences. This study contributes to the digital finance and fintech adoption literature by providing empirical evidence from a student population in a developing country context. The findings also offer practical implications for policymakers, educational institutions, and digital payment providers to prioritize digital financial literacy development as a key strategy for promoting sustainable cashless payment adoption.